Quantitative gas chromatographic method for the analysis of cis and trans fatty acid in margarines - Jumat Salimon; Talal Ahmed; Nadia Salih (Universiti Kebangsaan Malaysia, 2014)
Fats and oils in human diets are the main sources of essential fatty acids for the body. However, there is a mounting concern about the intake of foods containing trans fatty acids (TFAs) due to their deleterious effects on human. Thus, the accurate detection of fatty acids (FAs) and TFAs is needed to control and correct nutrition labeling in dietary fat samples. Accordingly, a method for the identification and quantification of FAs and TFAs in food fats by gas chromatography (GC) based on the extraction of lipids and derivatization using base catalyzed followed by trimethylsilyl-diazomethane (TMS-DM) was developed. The proposed method was evaluated to standard mixture of oleic acid (OA) (C18:1 cis 9) and Elaidic acid (EA) (C18:1 trans 9) and its application to three samples of commercial margarines was demonstrated. Based on the results obtained, recovery values (R) from all the samples were close to 100%. Repeatability (RSD) values ranged between 0.78 and 2.47%, while Reproducibility (RSD) values ranged between 1.14 and 3.65%. Consequently, the proposed method is sensitive, accurate and suitable for FAs and TFAs analysis of food fats and oils and can be applied to nutritional, medicine and food studies.